Analisis Implementasi Three Way Matching Dalam Meningkatkan Kualitas Sistem Informasi Akuntansi (Pada CV Migaspro Energia) - Syafira , Rifa; Rizqi, Muhammad Nur; Rumiasih , N. A. (CV. ITTC INDONESIA, 2024)
The purpose of this study is to assess the implementation of Three Way Matching as well as the quality of CV Migaspro Energia's accounting information systems. Qualitative descriptive analysis was employed in the study. This study's data collection techniques included documentation, observation, and interviews. Based on the findings of the research, the finance department of CV Migaspro Energia implemented Three Way Matching and created three documents required for this process purchase order data, goods receipt data, and buy invoice data. Implementing Three Way Matching can help CV Migaspro Energia improve the quality of its accounting information systems. It can be seen from before and after use because by using this method, the problem of data discrepancies, payment errors, and lack of transparency in the audit process has rarely occurred in companies, whereas these problems frequently occurred in companies prior to this application, allowing the quality of the company's accounting information system to improve by producing reliable financial statements. The Three Way Matching process is still manual and not automated by the Three Way Matching support program.